Ageing and recurrent episodes of neuroinflammation promote progressive experimental autoimmune encephalomyelitis in Biozzi ABH mice. Issue 2 (9th August 2016) - Peferoen, Laura A. N.; Breur, Marjolein; van de Berg, Sarah; Peferoen‐Baert, Regina; Boddeke, Erik H. W. G. M.; van der Valk, Paul; Pryce, Gareth; van Noort, Johannes M.; Baker, David; Amor, Sandra
Summary: Current therapies for multiple sclerosis (MS) reduce the frequency of relapses by modulating adaptive immune responses but fail to limit the irreversible neurodegeneration driving progressive disability. Experimental autoimmune encephalomyelitis (EAE) in Biozzi ABH mice recapitulates clinical features of MS including relapsing–remitting episodes and secondary‐progressive disability. To address the contribution of recurrent inflammatory events and ageing as factors that amplify progressive neurological disease, we examined EAE in 8‐ to 12‐week‐old and 12‐month‐old ABH mice. Compared with the relapsing–remitting (RREAE) and secondary progressive (SPEAE) EAE observed in young mice, old mice developed progressive disease from onset (PEAE) associated with pronounced axonal damage and increased numbers of CD3 + T cells and microglia/macrophages, but not B cells. Whereas the clinical neurological features of PEAE and SPEAE were comparable, the pathology was distinct. SPEAE was associated with significantly reduced perivascular infiltrates and T‐cell numbers in the central nervous system (CNS) compared with PEAE and the acute phase of RREAE. In contrast to perivascular infiltrates that declined during progression from RREAE into SPEAE, the numbers of microglia clusters remained constant. Similar to what is observed during MS, the microglia clusters emerging during EAE were associated with axonal damage and oligodendrocytes expressing heat‐shock protein B5, but not lymphocytes. Taken together, our data reveal that the course of EAE is dependent on the age of the mice. Younger mice show a relapsing–remitting phase followed by progressive disease, whereas old mice immediately show progression. This indicates that recurrent episodes of inflammation in the CNS, as well as age, contribute to progressive neurological disease. Abstract : Current therapies for multiple sclerosis (MS) reduce relapses by modulating adaptive immune responses but fail to limit the irreversible neurodegeneration driving progressive disability associated with age and innate immune cell activation. Our data show that the course of experimental autoimmune encephalomyelitis (EAE), an animal model of MS, is also dependent on age, as younger mice develop relapsing–remitting disease followed by a progressive phase, whereas old mice immediately develop progressive neurological disease. Hence this model is more relevant to study mechanisms of and therapeutic approaches for progressive MS.